Modeling 3D tumor invasiveness to modulate macrophage phenotype in a human-based hydrogel platform - Monteiro, Cátia F. (2024)
The immune system is a pivotal player in determining tumor fate, contributing to the immunosuppressive microenvironment that supports tumor progression. Considering the emergence of biomaterials as promising platforms to mimic the tumor microenvironment, human platelet lysate (PLMA)-based hydrogel beads are proposed as 3D platforms to recapitulate the tumor milieu and recreate the synergistic tumor-macrophage communication. Having characterized the biomaterial-mediated pro-regenerative macrophage phenotype, an osteosarcoma spheroid encapsulated into a PLMA hydrogel bead is explored to study macrophage immunomodulation through paracrine signaling. The culture of PLMA-Tumor beads on the top of a 2D monolayer of macrophages reveals that tumor cells triggered morphologic and metabolic adaptations in macrophages. The cytokine profile, coupled with the upregulation of gene and protein anti-inflammatory biomarkers clearly indicates macrophage polarization toward an M2-like phenotype. Moreover, the increased gene expression of chemokines identified as pro-tumoral environmental regulators suggest a tumor-associated macrophage phenotype, exclusively stimulated by tumor cells. This pro-tumoral microenvironment is also found to enhance tumor invasiveness ability and proliferation. Besides providing a robust in vitro immunomodulatory tumor model that faithfully recreates the tumor-macrophage interplay, this human-based platform has the potential to provide fundamental insights into immunosuppressive signaling and predict immune-targeted response.